COMBATIENTES EXTRANJEROS EUROPEOS EN SIRIA E IRAK: ¿ES PROBABLE QUE ATAQUEN A SU REGRESO? (Revista del Instituto Español de Estudios Estratégicos, 2018)
The study examined the likelihood whereby EU citizens who were orstill are fighting in the Syrian civil conflict or the Iraqi insurgency couldperpetrate an attack upon return. A comparative analysis was conductedamong the United Kingdom, France, Germany and Belgium in terms ofcapability, intent and opportunity of their foreign fighters and returnees topose a threat. It is argued that independent attacks by returnees are morelikely to happen in France than in the UK, Germany and Belgium due tothe fact that French extremist networks appear to have distanced themselvesfrom Syria-related issues in order to avoid being banned and go undetectedby the authorities.